Decrease in Antioxidant Status of Plasma and Erythrocytes from Geriatric Population. Issue 6 (21st May 2013) - Kumawat, Manjulata; Sharma, Tarun Kumar; Singh, Ishwar; Singh, Neelima; Singh, Sanjeev Kumar; Ghalaut, Veena Singh; Shankar, Vijay; Vardey, Satish Kumar
Abstract : Background : Ageing is associated with an accumulation of free radical damage, which leads to physiological and clinical modifications. The study aims to find out the status of lipid profile, antioxidant enzymes, malondialdehyde in geriatric population. Patients/methods : The study was conducted on 150 subjects (75 healthy control between the ages of 20–30 years and 75 elderly subjects between ages of 50–70 years as cases). The following parameters were analyzed using the standard reference methods: lipid profile, reduced glutathione, glutathione peroxidase, glutathione reductase, catalase, superoxide dismutase and malondialdehyde. Results : The present study was conducted to estimate the oxidative stress parameters in geriatric population. Highly significant increase in total cholesterol (TC), triglyceride (TG), LDL-cholesterol (LDL-C), VLDL-cholesterol (VLDL-C), malondialdehyde, catalase and decrease in high density lipoprotein cholesterol (HDL-C), reduced glutathione, glutathione peroxidase, glutathione reductase, superoxide dismutase was observed in geriatrics when compared with their younger counterparts. Conclusion : This study concluded that there is enhanced oxidative stress and decreased antioxidant defence in geriatrics as compared to younger subjects which could play an important role in ageing. Dyslipidemia has become one of the important risk factors for the increasing prevalence of cardiovascular diseases. There is lack of awareness on the relationship between blood lipids and the risk of cardiovascular diseases in geriatric population. The strategy of early prevention should be adopted against dyslipidemia.